1972
DOI: 10.1139/g72-119
|View full text |Cite
|
Sign up to set email alerts
|

CORRELATED RESPONSE TO NATURAL SELECTION IN LABORATORY POPULATIONS OFTRIBOLIUM CASTANEUM

Abstract: Intra- and interpopulation correlations between productivity and period of productivity were significant. One-day-old pupae and one-day-old adult weights were not associated with productivity. The intrapopulation correlation coefficients between productivity and developmental time were found to be significant. However, all of them (except one) were negative. Significant interpopulation relationships were noted when productivity was correlated with 13-day larval weight and with developmental time. Positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The eight strains used in the present investigation are the same as those whose variations in body weight, development and productivity have been previous ly studied by Soliman and H ardin [1971,1972] and Soliman |1972c]. Their papers may be consulted for details about the source, geographic origin and past culturing techniques.…”
Section: Methodsmentioning
confidence: 99%
“…The eight strains used in the present investigation are the same as those whose variations in body weight, development and productivity have been previous ly studied by Soliman and H ardin [1971,1972] and Soliman |1972c]. Their papers may be consulted for details about the source, geographic origin and past culturing techniques.…”
Section: Methodsmentioning
confidence: 99%
“…It was in analysing Tribolium data that W.C. Allee formulated the theory that has become known as the ‘Allee effect’, an optimum density for initial population growth (Allee 1931 ; Park 1932 ), whereby at small population sizes mean individual fitness is reduced (Stephens et al 1999 ). The rate of population growth has also been quantified across a range of environmental factors, including food quality and composition (e.g., Wong and Lee 2011 ), as well as life history parameters such as development time, with populations of fast-developing individuals able to grow more quickly than those in which individuals develop more slowly (Soliman 1972 ).…”
Section: Population Dynamicsmentioning
confidence: 99%
“…reported a reduction of 1.11 pupae per generation when selecting for pupa weight . In addition , Soliman (1972Soliman ( , 1982 indicated that reproductive ability could be reduced if animals were selected for pupa weight. The reason for finding a smaller correlated response of family size in our experiment might be due to the slight increasing trends for family size until generation seven, more over between generation eight and seventeen there was very little upward or downward trend for all four lines.…”
Section: Introductionmentioning
confidence: 99%
“…A negative phenotypic and genetic correlation between larval and pupa weight was reported ; twas -.05 ± .04 and rG was -.14 ± .14 in the line age 1, and twas -.26 ± .04 and rG was -.40 ± .12 in the line age 2, and twas -.11 ± .04 and rG -.09 ± .13 in the line age 3. Soliman (1972) investigated the correlated response of productivity to natural selection using Tribolium at constant environmental conditions of 33°C with 70% RH and a diet of 95% wheat flour with 5% dried yeast. He found a significant effect of developmental time (pupation time and adult emergence time) on the productivity (number of pupa and number of larvae at 13-day); the longer pupation time and longer adult emergence time decreased the total number of larvae at 13-day and the total number of pupa.…”
mentioning
confidence: 99%